RESPONS SISWA TERHADAP PEMBELAJARAN MENULIS TEKS PUISI MENGGUNAKAN MODEL PJBL BERBANTUAN MEDIA CANVA PADA KELAS VIII - Novita Mulyani; Wikanengsih; Yesi Maylani Kartiwi (IKIP Siliwangi, 2026)
This research is backed by limited diction, difficulty in expressing feelings and thoughts, lack of understanding of the structure of poetry, difficulty in finding interesting ideas or themes to be used as poetry material, feeling less confident and unmotivated in writing poetry texts. This research aims to find out the student's response to learning to write poetry texts using the PjBL model with the help of canvas media in class VIII students. This research uses a descriptive qualitative method. Data collection techniques in this study were carried out through the spread of anget. The subjects in this study are junior high school students of class VIII. Poetry is a type of literary work that comes from the expression and feelings of a poet, using language that is bound by rhythm, matra, rhyme, as well as the arrangement of meaningful lyrics and verses. The results of the analysis showed that the presentation rate was 86%, so students felt positive during the learning process. Based on the results that have been listed, it can be concluded that the PjBL model with the help of canvas media can be used in learning to write poetry texts, this is evidenced by the very positive student response.